Assessment of the potential and application of Be12O12 nanocage for removal of ciprofloxacin from water employing density functional theory - Qaisar Ali; Abdul Shakoor; Gul Rehman; Munir Ur Rehman; Momin Khan; Rashid Ahmad; Iftikhar Ahmad; Abdullah F. AlAsmari; Fawaz Alasmari (Scientific Reports)
Abstract The modern world is facing the issue of emerging pollutants for its sustainable development. We report a detailed study on the abatement of ciprofloxacin (CIP) by Be12O12 nanocage. Five different geometries of Be12O12 nanocage with CIP i.e., Com-A, Com-B, Com-C, Com-D and Com-E are optimized. All the complexes show chemisorption with the highest adsorption energies (E ads) of − 39.86 kcal/mol for Com-E followed by Com-A, Com-B, Com-C and Com-D without any structural change. The O and F atoms of ciprofloxacin (CIP) interacts strongly with the Be atoms of the nanocage respectively. Charge transfer from the nanocage to CIP reveals strong interaction in all the optimized complexes, with maximum charge transfer of -0.199 e for Com-E with the smallest bond lengths of 1.52 Å and 1.63 Å. The decrease in the bandgap of the optimized geometries witnesses increase in the sensing ability of the adsorbent and demonstrates strong interaction between the adsorbent and adsorbate supporting the adsorption energies. The positive values of Hb and ∇2ρb for all complexes reveals strong interaction of electrostatic nature between CIP and Be12O12 nature which is supported by different tools of DFT. The overall study suggests Be12O12 an efficient, reusable adsorbent for the purification of water from CIP and therefore Be12O12 can be used effectively to eliminate antibiotics from water.